Harnessing the human gut microbiota: an emerging frontier in combatting multidrug-resistant bacteria - Ding, Wenwen; Cheng, Yiwen; Liu, Xia; Zhu, Zhangcheng; Wu, Lingbin; Gao, Jie; Lei, Wenhui; Li, Yating; Zhou, Xin; Wu, Jian; Gao, Yongtao; Ling, Zongxin; et al. (Frontiers in Immunology, 2025)
Antimicrobial resistance (AMR) has become a major and escalating global health threat, undermining the effectiveness of current antibiotic and antimicrobial therapies. The rise of multidrug-resistant bacteria has led to increasingly difficult-to-treat infections, resulting in higher morbidity, mortality, and healthcare costs. Tackling this crisis requires the development of novel antimicrobial agents, optimization of current therapeutic strategies, and global initiatives in infection surveillance and control. Recent studies highlight the crucial role of the human gut microbiota in defending against AMR pathogens. A balanced microbiota protects the body through mechanisms such as colonization resistance, positioning it as a key ally in the fight against AMR. In contrast, gut dysbiosis disrupts this defense, thereby facilitating the persistence, colonization, and dissemination of resistant pathogens. This review will explore how gut microbiota influence drug-resistant bacterial infections, its involvement in various types of AMR-related infections, and the potential for novel microbiota-targeted therapies, such as fecal microbiota transplantation, prebiotics, probiotics, phage therapy. Elucidating the interactions between gut microbiota and AMR pathogens will provide critical insights for developing novel therapeutic strategies to prevent and treat AMR infections. While previous reviews have focused on the general impact of the microbiota on human health, this review will specifically look at the latest research on the interactions between the gut microbiota and the evolution and spread of AMR, highlighting potential therapeutic strategies.